2015
DOI: 10.3389/fmicb.2015.01454
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Composition and Survival on Sahara Dust Particles Transported to the European Alps

Abstract: Deposition of Sahara dust (SD) particles is a frequent phenomenon in Europe, but little is known about the viability and composition of the bacterial community transported with SD. The goal of this study was to characterize SD-associated bacteria transported to the European Alps, deposited and entrapped in snow. During two distinct events in February and May 2014, SD particles were deposited and promptly covered by falling snow, thus preserving them in distinct ochre layers within the snowpack. In June 2014, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
98
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 102 publications
(142 reference statements)
8
98
0
3
Order By: Relevance
“…Nanometer scaled fragments from biological particles are present in much higher concentrations and might have atmospheric implications (Pummer et al, 2012;Augustin et al, 2013;O'Sullivan et al, 2015;Fröhlich-Nowoisky et al, 2015;Wilson et al, 2015). Additionally, bacteria have been found in Saharan (Meola et al, 2015) and soil dust (Conen et al, 2011) aerosols, possibly influencing their ice nucleation activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer scaled fragments from biological particles are present in much higher concentrations and might have atmospheric implications (Pummer et al, 2012;Augustin et al, 2013;O'Sullivan et al, 2015;Fröhlich-Nowoisky et al, 2015;Wilson et al, 2015). Additionally, bacteria have been found in Saharan (Meola et al, 2015) and soil dust (Conen et al, 2011) aerosols, possibly influencing their ice nucleation activity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent knowledge suggests that the transported mineral and biological particles of large-scale dust storms affect cloud ice formation and precipitation processes, creating novel climate system feedbacks [7]. In particular, during winter, alien biological particles associated with large dust events may be deposited in vast numbers leaving persistent dust layers in the snowpack [8] that, at the highest elevations are preserved in the ice of glaciers. Such permanently frozen environments harbour a variety of viable microorganisms [9] that have been deposited over centuries [10], but it was rarely shown that they can persist in the new habitat after the snowpack was melted [11].…”
Section: Introductionmentioning
confidence: 99%
“…are common in both the Kuytun 51 and Qiangyong glaciers but only Rhodoferax ( Betaproteobacteria ) is dominant in the Kuytun 51 glacier (Xiang et al, 2010). The changes of the dominant bacteria in glaciers are mainly influenced by processes such as wind deposition (airborne or aerosol-associated microorganisms by prevailing winds and dust-associated microorganisms by dust storm events), precipitation deposition (microbial deposition with snow, wet-deposition), and post-deposition by microbial growth in the warming seasons on the glacier surface snow (Xiang et al, 2009; Price and Bay, 2012; Bottos et al, 2014; Peter et al, 2014; Meola et al, 2015; Miteva et al, 2015; Pearce et al, 2016). Among these processes, post-deposition has an important role in the transition of microbial communities in glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown influences of post-deposition on the transition of communities from the light-sensitive cyanobacteria dominated in the surface snow to the non-light-sensitive bacteria buried in the subsurface snow (Xiang et al, 2009). The geographic differences in microbial communities across the mountain glaciers could be attributed to the mountain barriers, which might control the microbial deposition by changing the prevailing wind directions and moisture sources; while the geographic patterns of the dominant microbial colonizers in glaciers might be also influenced by the local climatic and environmental conditions (Nkem et al, 2006; Xiang et al, 2009, 2010; Demetras et al, 2010; Meola et al, 2015). …”
Section: Introductionmentioning
confidence: 99%